Радиопротекторный эффект комплексного витаминного препарата «Веторон» в культуре лимфоцитов периферической крови человека - Шеметун, Е.В.; Талан, О.А.; Пилинская, М.А. (Фактори експериментальної еволюції організмів, 2013)
Aim. Investigation of the effect of complex vitamin medical product «Vetoron» on the level of chromosomal damages induced by X-ray irradiation in vitro in human peripheral blood lymphocytes. Methods. Cultivation of peripheral blood lymphocytes received from ten conditionally healthy volunteers during 48 hours; X-ray irradiation of whole blood before cultivation in a dose 1 Gy; treatment of whole blood by «Vetoron» (complex of water-soluble forms of vitamins A, E, C) in concentration 40 mkg/ml 1 hour before irradiation; G-banding staining of metaphase chromosome slides; scoring of slides under the microscope (cytogenetic analysis); identification of the full range of chromatid and chromosome aberration types. Results. The use of complex vitamin medical product «Vetoron» before X-ray irradiation of human whole blood in vitro significantly reduced radioinduced cytogenetic effect in cultured human peripheral blood lymphocytes. Conclusions. The data received indicate radioprotective effect of «Vetoron» established by cytogenetic criteria.